Breaking Bad News in Obstetrics and Gynecology: We Must Talk About It - Ribeiro, Luísa Silva de Carvalho; D'Abreu, Bárbara Flecha; Santiago, Aline Evangelista; Cândido, Eduardo Batista; Romão, Gustavo Salata; de Sá, Marcos Felipe Silva; da Silva Filho, Agnaldo Lopes (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Breaking bad news is common in obstetrics and gynecology (ob-gyn). However, it is difficult, and few doctors receive training on how to deal with this situation. This narrative review aims to gather, analyze, and synthesize part of the knowledge on the area, focused on Ob-Gyn. Among the 16 selected articles, two are randomized controlled intervention studies, and most studies refer to obstetrics. The results found by us pointed out that simulation, feedback/debriefing, lectures, and protocols could improve doctors' performance in communicating bad news. For patients, the context and how the information is transmitted seem to impact more than the content of the news. Ob-Gyn doctors could benefit from specific protocols and education, given the specialty's particularities. There is a lack of evidence about the most effective way to conduct such training. Finding validated ways to quantify and classify studies' results in the area, which would allow for the objective analysis of outcomes, is one of the biggest challenges concerning this topic.
Keywords: communication; bad news; obstetrics; gynecology; medical education